SUSTAINING TRADITIONAL MARKETS IN THE DIGITAL ERA: THE ROLE OF TECHNOLOGY IN MODERATING MARKETPLACE AND CONSUMER BEHAVIOR IMPACTS IN RURAL INDONESIA - Verliani Dasmaran; Novelia Kiki Permata Sari; Sevi Maulana Safar (ZILLZELL MEDIA PRIMA, 2025)
The rapid growth of the marketplace driven by digital technology has increased consumer appeal, but is inversely proportional to the decline in the turnover of non-food traditional market traders, especially in the Panimbang Market. This study aims to analyze the influence of marketplace and consumer behavior on the sustainability of traditional markets by considering the role of technological sophistication as a moderation variable in Panimbang Market, Banten. The main problem in this study lies in the existence of research gaps. This study uses a descriptive quantitative approach by collecting data through questionnaires that are distributed directly in physical form. The sampling technique used was non-probability sampling with the quota sampling method, where the research population included all traders of the Panimbang Market, and the sample number was set as 135 respondents. Data analysis was carried out using SmartPLS4 software version 4.1.1.4. The results of the study show that the marketplace and consumer behavior have a positive and significant effect on the sustainability of traditional markets. However, technological sophistication does not significantly moderate the influence of the marketplace, while consumer behavior has a significant negative effect, which indicates that the limitations of merchant digital literacy weaken the positive impact of consumer behavior on the sustainability of traditional markets.